Analisis Kinerja Keuangan Pada PT. Budhian Indra di Kota Dumai - Yusrialis Yusrialis; Ilham Kurniawan (Lembaga penelitian dan pengabdian kepada masyrakat, 2012)
This research is done on PT. Budhian Indra who gets address be cleared a root By Cempedak Dumai Riau’s Western. In this research one becomes population be PT’s financial statement. Budhian Indra. Data that is taken bases descriptive method which is analyse data as write-up as balance, balance reporting, ekuitas’s changed reporting, and cash flow reporting then linked by real situation and linked by supportive theory and does internal compare with compare finance ratio on each period. Data type that utilized by writer is skunder which is as PT’s financial statement. Budhian Indra as write-up as balance, balance reporting, ekuitas’s changed reporting, and cash flow reporting of year 2006,2007,2008,2009,2010. Of research result that gotten by its result, can be concluded that PT’s financial statement. Unstable Budhian Indra. It can be seen from fluktasi what do happen on PT’s financial position. Budhian Indra